BIOLOGY AND FISHERY OF THE BUTTERFLY RAY, GYMNURA POECILURA (SHAW) FROM THE PALK BAY AND GULF OF MANNARBIOLOGY AND FISHERY OF THE BUTTERFLY RAY, GYMNURA POECILURA (SHAW) FROM THE PALK BAY AND GULF OF MANNAR - James, P S B R (Indian Journal of Fisheries, 2011)
A number of species of rays are of commercial importance at several places along the Indian Coast, forming popular food of the conmion man. They are consumed both in the fresh and cured states. Although the meat is generally considered to be of a low quality, for which reason it is sold very cheap, the flesh of certain species (e.g., Aetobatus narinari) is esteemed as a delicacy.